Sculpting foraminifera - Maric, Filip; Poto, Margherita; Zimmermann, Heike Jane; Panieri, Giuliana (Septentrio Educational, 2023)
Focus: To appreciate the biodiversity of the Arctic Ocean and ocean floor, with a particular focus on lesser-known species like foraminifera. Learning objectives: In this activity, pupils will identify (one, two, or several) foraminifera species living at or close to the Arctic Ocean floor and sculpt them using modelling clay. Key words: Foraminifera, Benthic, Planktonic.